THE EFFECTIVENESS OF POSYANDU CADRE EMPOWERMENT IN ENHANCING POSYANDU CADRE'S KNOWLEDGE AS A STUNTING PREVENTION EFFORT - Rospiati ,; Dwi Prihatin Era ,; Ega Ersya Urnia , (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Stunting remains a significant nutritional challenge in Indonesia. Posyandu, a community-based healthcare initiative, plays a crucial role in stunting prevention. However, it is essential to empower the posyandu cadres to effectively address this issue. This study aims to assess the impact of empowering posyandu cadres on their knowledge, specifically in preventing stunting. This research employs a quasi-experimental design, utilizing a One-Group pre-posttest approach to evaluate the influence of educational interventions on cadre knowledge. The study population consists of 70 posyandu cadres within the Kaubun Health Center's working area. The entire population was included as study participants. Data collection involved the use of questionnaires, PowerPoint presentations (PPT), and leaflets. Statistical analysis was conducted using the Wilcoxon test. The statistical analysis using the Wilcoxon test yielded a p-value of 0.000, indicating a significant positive effect of education on the knowledge of posyandu cadres regarding stunting. Education has a notable impact on enhancing the knowledge of posyandu cadres in relation to stunting prevention. The assessment of posyandu cadre knowledge revealed an increase in their average scores related to stunting prevention. This improvement is evident in the average scores before and after receiving education, with an increase of 1.98.